2018
DOI: 10.1111/jch.13216
|View full text |Cite
|
Sign up to set email alerts
|

Guidance on home blood pressure monitoring: A statement of the HOPE Asia Network

Abstract: Hypertension is an important modifiable cardiovascular risk factor and a leading cause of death throughout Asia. Effective prevention and control of hypertension in the region remain a significant challenge despite the availability of several regional and international guidelines. Out‐of‐office measurement of blood pressure (BP), including home BP monitoring (HBPM), is an important hypertension management tool. Home BP is better than office BP for predicting cardiovascular risk and HBPM should be considered fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
92
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(92 citation statements)
references
References 51 publications
0
92
0
Order By: Relevance
“…To avoid reporting bias, BP data were automatically stored in device memory, then entered into the study database by a physician or nurse. Home BP measurements were performed according to the Expert Panel Consensus Recommendations for HBPM (the HOPE Asia Network), 26,27 which modified guidelines from the European Society of Hypertension (ESH), 11,12 Japanese Society of Hypertension (JSH), 13 and the Korean Society of Hypertension, 37 and the China consensus document on HBPM. 38 Patients measured their BP at home using the device provided twice in the morning (morning home BP) and twice at bedtime (evening home BP) as follows.…”
Section: Bp Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…To avoid reporting bias, BP data were automatically stored in device memory, then entered into the study database by a physician or nurse. Home BP measurements were performed according to the Expert Panel Consensus Recommendations for HBPM (the HOPE Asia Network), 26,27 which modified guidelines from the European Society of Hypertension (ESH), 11,12 Japanese Society of Hypertension (JSH), 13 and the Korean Society of Hypertension, 37 and the China consensus document on HBPM. 38 Patients measured their BP at home using the device provided twice in the morning (morning home BP) and twice at bedtime (evening home BP) as follows.…”
Section: Bp Measurementsmentioning
confidence: 99%
“…4,13,15,16 Again, this is likely to be of greater importance in Asia due to the presence of Asian-specific characteristics in the 24-hour BP profile. 13,[25][26][27] There are several studies highlighting the importance of home BP for improving cardiovascular prognosis. 17,[20][21][22][23][24] A self-measured home BP-guided strategy has been stressed as the most effective practical approach of the management of hypertension in Asia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current use of HBPM in Indonesia is based on guidance from the HOPE Asia Network and the 2019 Indonesian Society of Hypertension (InaSH) . The new InaSH hypertension consensus was launched at the society's 2019 meeting, which highlighted the vital role of HBPM and provided guidelines for its use .…”
Section: Positioning Of Hbpm In the Indonesian Hypertension Guidelinesmentioning
confidence: 99%
“…Home blood pressure (BP) measurement is widely used and recommended for the management of hypertension. [1][2][3][4][5] Several studies have reported that home BP measured by an automatic cuff-oscillometric device has greater predictive power for cardiovascular (CV) outcomes than clinic BP. 6,7 Moreover, there is a common phenomenon known as masked hypertension (MHT) defined by out-of-clinic BP in the hypertensive range among individuals with normal-range clinic BP.…”
Section: Introductionmentioning
confidence: 99%